PERAN KELOMPOK TANI DANAU SEPAKAT TERHADAP ANGGOTA DI JORONG LADANG NAGARI KOTO SANI KECAMATAN X KOTO SINGKARAK - Fitri, Ayani; Sarbatinil, Sarbatinil; Yuhelna, Yuhelna (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
Agriculture is an inseperable part of human life, agriculture is an activity of utilizibg biological resources carried out by humans to produce food, industrial raw materials or energy of energy sources, and manage their environment, while agricultura bussinises actors called farmer™s, in helping farmer™s to overcome problems in conducting farming and help improve the welfare o farmer™s, the gonverment formed a farmer group organization which is under the auspices of the agricultural service. The purpose of this analysis is to find out the rol of the Danau Sepakat farmer group towards members in Jorong Ujung Ladang, Nagari Koto Sani, Kecematan X Koto Singkarak. The approach with descriptive research type, the techniques used in this research are observation, interviews, and document study. The informants in this study were the administrators of the Danau Sepakat  farmer group, members of the  Danau Sepakat farmer group, and Mr. Jorong Ujung Ladang, Nagari Koto Sani. Based on the result of field analysis it can be concluded that the lake concluded that the Danau Sepakat farmer group had an effect on members including in the form of 1. Increasing the knowledge og group members farming, 2. Reducing member™s capital in conducting farming, 3. Inreasing farmer™s income, 4. Reducing abandoned land.